Становлення технологічного підходу - новаційний напрямок розвитку криміналістики - Тищенко, Валерий Владимирович; Tishchenko, Valeryi V.; Тіщенко, Валерій Володимирович; Барцицька, А. А. (My University, 2012)
Research is directed on definition of essence of a technological approach, and also its theoretical and practical value. It is proved historical conditionality of a technological approach in the criminalistics which emergence corresponds to the general laws and the priority directions of development of a science. From positions of a technological approach the direction of research of object of criminalistics as qualitatively new form of scientific knowledge and functioning of difficult systems – criminal activity and activities for investigation of crimes is defined.
Тіщенко В. В. Становлення технологічного підходу - новаційний напрямок розвитку криміналістики / В. В. Тіщенко // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. - Вип. 68. - С. 560-566.
Keywords: криміналістична технологія; технологічний підхід; системний підхід; функціональний підхід; діяльнісний підхід; криминалистическая технология; технологический подход; системный подход; функциональный подход; деятельностный подход; criminalistic technology; technological approach; system approach; functional approach; activity approach